Evaluation of Antioxidant Activity and Genotoxicity of Alcoholic and Aqueous Beverages and Pomace Derived from Ripe Fruits of Cyphomandra betacea Sendt - Ordóñez, Roxana Mabel (2010)
Cyphomandra betacea ripe fruits can be a source of value-added byproducts and products such as antioxidant supplements, ingredients for food processing or alternative medical products. The aims of the present study were to obtain different preparations of C. betacea fruits, such as juice, decoction, and maceration and to characterize them in terms of microbiological stability, sensorial and chemical parameters, antioxidant potential (DPPH and ABTS•+ radical scavenging, β-carotene bleaching, nitrite scavenging activities), capacity to prevent oxidative stress-induced cell death, and genotoxicity. The best antioxidant activity was found in C. betacea fruit maceration, probably as a consequence of the high flavonoid and anthocyanin content. Nevertheless, all preparations analyzed proved to be good as free radical scavengers (SC50 values between 1.88 and 44 μg/mL) and exerted protection against β-carotene oxidation. Total phenolic compounds and flavonoids showed a better correlation than anthocyanins with the free radical scavenging effect of the assayed foods. The insoluble matters (pomace) obtained after juice preparation showed antioxidant activity by quenching free radicals. Furthermore, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) reduction assay showed that C. betacea preparations prevent oxidative stress-induced cell death in HepG2 cells in a dose-dependent manner. Salmonella microsome assays show no mutagenic effect. The data presented in this study demonstrate that C. betacea ripe fruits, aqueous and ethanolic preparations, and pomace may be a good source of antioxidant compounds in nutraceutical or functional-food products.